Moisture-absorbing, sweat-releasing and antibacterial titanium fiber fabric and preparation method thereof

By grafting modification and loading nanotitanium dioxide on nylon fiber fabrics, the problems of insufficient moisture-absorbing, antibacterial and flame retardant properties of nylon fiber fabrics are solved, and efficient moisture-absorbing and antibacterial effects are achieved.

CN120556274AActive Publication Date: 2025-08-29GUANGDONG YUDIAN SUPPLY CHAIN MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510728555.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-03
Publication Date
2025-08-29
Estimated Expiration
2045-06-03

AI Technical Summary

Technical Problem

Nylon fiber fabric has poor moisture absorption, antibacterial properties and flame retardant properties, which limits its application in high-end clothing and apparel.

Method used

By grafting 2,4-bis(N,N'-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-homotriazine and tetrabutyl titanate solution to the nylon fiber fabric, amide bonds, imino groups and hydroxyl groups are formed, and combined with high-temperature hydrothermal method to load nanotitanium dioxide, the hydrophilicity and antibacterial properties of the fabric are improved.

Benefits of technology

It significantly improves the moisture absorption, antibacteriality and flame retardancy of the fabric, improves the moisture rebate rate and extreme oxygen index, and enhances the antibacterial rate of E. coli.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics, and discloses a moisture-absorbing, sweat-releasing and antibacterial titanium fiber fabric and a preparation method thereof.2, 4-di-(N, N '-diethylamino)-6-[N-(3-aminopropyl) methacrylamide] triazine is used for conducting graft modification on a polyamide fiber fabric, so that the moisture-absorbing, sweat-releasing and antibacterial titanium fiber fabric is obtained. Hydrophilic amido bonds, imino groups and a large number of hydroxyl groups are grafted to the surface of the fabric, so that the hydrophilicity and moisture regain of the fabric are remarkably improved, and the moisture absorption and sweat releasing performance of the fabric can be improved. Meanwhile, the limit oxygen index and the flame retardant property are improved. A large number of hydroxyl groups on the surface of the chinlon fabric can interact with hydroxyl groups on the surface of a titanium dioxide precursor generated by hydrolysis of tetrabutyl titanate, so that generated nano titanium dioxide can be uniformly loaded on the surface of the fabric, more photocatalytic antibacterial sites are exposed, and the antibacterial performance of the fabric is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fabrics, in particular to a moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric and a preparation method thereof. Background Art

[0002] Nylon fiber fabrics are known for their toughness, abrasion resistance, and high elasticity, making them widely used. However, traditional nylon fabrics have a low moisture regain, which affects their moisture absorption and perspiration wicking properties. Furthermore, their poor antibacterial and flame retardant properties hinder their practical application in high-end apparel and accessories. Currently, the main methods for improving the moisture absorption and antibacterial properties of nylon fabrics include finishing with finishing agents and chemical grafting modification. Common chemical grafting monomers include acrylic acid, hydroxyethyl acrylate, and acrylamide.

[0003] Nano-titanium dioxide is non-toxic and pollution-free, has a simple preparation method, and has strong antibacterial properties. It is widely used in fabrics, plastics, rubber and other materials. Loading nano-titanium dioxide onto the surface of fabrics can give them excellent antibacterial properties. However, nano-titanium dioxide is easy to agglomerate and has poor dispersion on the surface of fabrics, which will affect its antibacterial properties. Summary of the Invention

[0004] (1) Technical problems solved: In response to the shortcomings of the existing technology, the present invention provides a moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric and a preparation method thereof, which solves the problems of poor moisture-absorbing, perspiration-wicking, antibacterial and flame-retardant properties of nylon fiber fabrics.

[0005] (II) Technical Solution: A method for preparing a moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric: (1) Add N-(3-aminopropyl)methacrylamide hydrochloride and 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine to 1,4-dioxane, and add sodium carbonate aqueous solution dropwise. After the reaction, cool and filter. The filtrate is rotary evaporated. The crude product is recrystallized from ethanol to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine.

[0006] (2) The cleaned nylon fiber fabric is added to an aqueous solution of potassium persulfate for pre-reaction, and then the fabric is added to an aqueous solution containing 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-isotriazine, and the bath ratio A is adjusted to carry out a grafting reaction. Finally, the fabric is added to deionized water, boiled, washed with water, and dried to obtain a moisture-absorbing and perspiration-wicking nylon fiber fabric.

[0007] (3) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution, and a moisture-absorbing and perspiration-resistant nylon fiber fabric was added, and the bath ratio B was adjusted. After two immersion and two rolling treatments, the fabric was added to deionized water, and the bath ratio C was adjusted. After the reaction, the fabric was taken out, washed with ethanol and water, and dried to obtain a moisture-absorbing and perspiration-resistant antibacterial titanium fiber fabric.

[0008] Furthermore, the molar ratio of N-(3-aminopropyl)methyl acrylamide hydrochloride to 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine in (1) is (1-1.2):1.

[0009] Furthermore, the reaction temperature in (1) is 75-85°C, and the reaction time is 6-10 hours.

[0010] Furthermore, the concentration of the aqueous solution of potassium persulfate in (2) is (0.01-0.025) mol / L.

[0011] Furthermore, the bath ratio A in (2) is 1:(35-50).

[0012] Furthermore, the temperature of the pre-reaction in (2) is 70-80°C, and the reaction time is 20-40 min.

[0013] Furthermore, the concentration of the aqueous solution of 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-s-triazine in (2) is (0.5-1.5) mol / L.

[0014] Furthermore, the grafting reaction temperature in (2) is 65-80°C, and the reaction time is 2-3h.

[0015] Furthermore, (2) the mass fraction of the tetrabutyl titanate solution is 20-30%.

[0016] Furthermore, the bath ratio B is 1:(30-40), and the bath ratio C is 1:(30-50).

[0017] Furthermore, the reaction temperature in (3) is 90-95°C, and the reaction time is 6-8h.

[0018] (3) Beneficial technical effects: The present invention utilizes 2,4-di-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methacrylamide] triazine containing alkenyl to graft-modify nylon fiber fabrics, grafting hydrophilic amide bonds, imino groups and a large number of hydroxyl groups to the surface of the fabric, significantly improving the hydrophilicity and moisture regain of the fabric, which is beneficial to improving the moisture absorption and perspiration wicking properties of the fabric.

[0019] The present invention grafts triazine groups onto the surface of nylon fabrics, which release nitrogen and other gases through thermal decomposition during combustion, thereby diluting the oxygen concentration, inhibiting combustion, and being beneficial to improving the limiting oxygen index and flame retardant properties.

[0020] The present invention introduces a large number of hydroxyl groups into the surface of nylon fabric. These large numbers of hydroxyl groups can interact with the hydroxyl groups on the surface of titanium dioxide precursor generated by hydrolysis of tetrabutyl titanate, thereby uniformly loading the titanium dioxide precursor onto the fabric surface. Further, through a high-temperature hydrothermal method, the generated nano-titanium dioxide can be uniformly loaded onto the fabric surface, exposing more photocatalytic antibacterial sites, thereby significantly improving the antibacterial rate and antibacterial performance of Escherichia coli. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0022] The preparation method of 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine is as follows: 18.4 g (0.1 mol) of cyanuric chloride is added to 50 mL of ethanol, and after stirring, 50 mL of an ethanol solution containing 22.05 g (0.21 mol) of triethanolamine and 22 g of triethylamine is added dropwise, stirred for 0.5 h, heated to 50° C., reacted for 5 h, cooled to room temperature, filtered, and the filtrate is rotary evaporated. The product is recrystallized from dichloromethane to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine, with the structural formula .

[0023] Example 1 (1) Add 80 mmol of N-(3-aminopropyl)methacrylamide hydrochloride and 80 mmol of 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine to 300 mL of 1,4-dioxane, and dropwise add 100 mL of an aqueous solution containing 192 mmol of sodium carbonate. Heat to 85°C, react for 6 h, cool, filter, and rotary evaporate the filtrate. The crude product is recrystallized from ethanol to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine. The preparation reaction formula is: .

[0024] (2) The cleaned nylon fiber fabric was added to a 0.01 mol / L potassium persulfate aqueous solution, heated to 75 °C, and reacted for 20 min. Then the fabric was added to a 0.5 mol / L 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-isotriazine aqueous solution with a bath ratio of 1:40. The solution was heated to 70 °C and reacted for 3 h. Finally, the fabric was added to deionized water and boiled for 10 min. The fabric was washed with water and dried to obtain a moisture-wicking nylon fiber fabric.

[0025] (3) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 20%, and moisture-absorbing and perspiration-wicking nylon fiber fabric was added at a bath ratio of 1:40. After two immersion and two rolling treatments, the rolling rate was 85%. Then the fabric was added to deionized water at a bath ratio of 1:30, heated to 95 °C, and reacted for 6 h. The fabric was taken out, washed with ethanol and water, and dried to obtain a moisture-absorbing and perspiration-wicking antibacterial titanium fiber fabric.

[0026] Example 2 (1) To 400 mL of 1,4-dioxane, 96 mmol of N-(3-aminopropyl)methacrylamide hydrochloride and 80 mmol of 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine were added dropwise, and 120 mL of an aqueous solution containing 216 mmol of sodium carbonate was added dropwise. The mixture was heated to 80°C and reacted for 10 h. The mixture was cooled, filtered, and the filtrate was rotary evaporated. The crude product was recrystallized from ethanol to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine.

[0027] (2) The cleaned nylon fiber fabric was added to a 0.018 mol / L potassium persulfate aqueous solution, heated to 70 °C, and reacted for 40 min. Then, the fabric was added to a 1 mol / L 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-isotriazine aqueous solution with a bath ratio of 1:50. The solution was heated to 65 °C and reacted for 3 h. Finally, the fabric was added to deionized water and boiled for 20 min. The fabric was washed with water and dried to obtain a moisture-wicking nylon fiber fabric.

[0028] (3) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 30%, and moisture-absorbing and perspiration-wicking nylon fiber fabric was added at a bath ratio of 1:30. After two immersion and two rolling treatments, the rolling rate was 90%. Then, the fabric was added to deionized water at a bath ratio of 1:50, heated to 90°C, and reacted for 8 hours. The fabric was taken out, washed with ethanol and water, and dried to obtain a moisture-absorbing and perspiration-wicking antibacterial titanium fiber fabric.

[0029] Example 3 (1) To 350 mL of 1,4-dioxane, 88 mmol of N-(3-aminopropyl)methacrylamide hydrochloride and 80 mmol of 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine were added dropwise, and 120 mL of an aqueous solution containing 224 mmol of sodium carbonate was added dropwise. The mixture was heated to 75 °C and reacted for 10 h. The mixture was cooled, filtered, and the filtrate was rotary evaporated. The crude product was recrystallized from ethanol to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine.

[0030] (2) The cleaned nylon fiber fabric was added to a 0.025 mol / L potassium persulfate aqueous solution, heated to 80 °C, and reacted for 20 min. Then the fabric was added to a 1.5 mol / L 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-isotriazine aqueous solution with a bath ratio of 1:35. The solution was heated to 80 °C and reacted for 2 h. Finally, the fabric was added to deionized water and boiled for 20 min. The fabric was washed with water and dried to obtain a moisture-wicking nylon fiber fabric.

[0031] (3) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 25%, and moisture-absorbing and perspiration-wicking nylon fiber fabric was added at a bath ratio of 1:40. After two immersion and two rolling treatments, the rolling rate was 85%. The fabric was then added to deionized water at a bath ratio of 1:40, heated to 95°C, and reacted for 7 hours. The fabric was taken out, washed with ethanol and water, and dried to obtain a moisture-absorbing and perspiration-wicking antibacterial titanium fiber fabric.

[0032] Comparative Example 1 is a nylon fiber fabric.

[0033] Comparative Example 2 (1) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 30%, and nylon fiber fabric was added with a bath ratio of 1:30. After two immersion and two rolling treatments, the rolling rate was 90%. Then the fabric was added to deionized water with a bath ratio of 1:50, heated to 80 °C, and reacted for 4 h. The fabric was taken out, washed with ethanol and water, and dried to obtain titanium fiber fabric.

[0034] Comparative Example 3 (1) The cleaned nylon fiber fabric was added to a 0.01 mol / L potassium persulfate aqueous solution, heated to 75 °C, and reacted for 20 min. The fabric was then added to a 0.5 mol / L hydroxyethyl acrylate aqueous solution with a bath ratio of 1:40, heated to 70 °C, and reacted for 3 h. Finally, the fabric was added to deionized water and boiled for 10 min. The fabric was washed with water and dried to obtain the grafted nylon fiber fabric.

[0035] (2) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 20%, and the grafted nylon fiber fabric was added with a bath ratio of 1:40. After two immersion and two rolling treatments, the rolling rate was 85%. Then the fabric was added to deionized water with a bath ratio of 1:30, heated to 95 °C, and reacted for 6 h. The fabric was taken out, washed with ethanol and water, and dried to obtain titanium fiber fabric.

[0036] Comparative Example 4 (1) Add 80 mmol of N-(3-aminopropyl)methacrylamide hydrochloride and 80 mmol of 2,4-di-(N,N'-diethylamino)-6-chlorotriazine (CAS registration number 580-48-3, structural formula: ), add 100 mL of an aqueous solution containing 192 mmol of sodium carbonate dropwise, heat to 85°C, react for 6 h, cool, filter, and rotary evaporate the filtrate. The crude product is recrystallized from ethanol to obtain 2,4-bis-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methacrylamide]triazine, the structural formula of which is .

[0037] (2) The cleaned nylon fiber fabric was added to a 0.01 mol / L potassium persulfate aqueous solution, heated to 75 °C, and reacted for 20 min. Then, the fabric was added to a 0.5 mol / L 2,4-di-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methylacrylamide]triazine aqueous solution with a bath ratio of 1:40, heated to 70 °C, and reacted for 3 h. Finally, the fabric was added to deionized water, boiled for 10 min, washed with water, and dried to obtain the grafted nylon fiber fabric.

[0038] (3) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution with a mass fraction of 20%, and the grafted nylon fiber fabric was added with a bath ratio of 1:40. After two immersion and two rolling treatments, the rolling rate was 85%. Then the fabric was added to deionized water with a bath ratio of 1:30, heated to 95 °C, and reacted for 6 h. The fabric was taken out, washed with ethanol and water, and dried to obtain titanium fiber fabric.

[0039] The moisture regain of fabrics is tested according to GB / T 9994-2018 standard.

[0040] Antibacterial performance was tested according to GB / T 23763-2009. The antibacterial rate is calculated as (C0 - C1) / C0 × 100%, where C0 is the number of viable bacteria (CFU) counted after incubation of the control sample (nylon fiber fabric of Comparative Example 1) under bright conditions. C1 is the number of viable bacteria (CFU) counted after incubation of the photocatalytic sample.

[0041] The flame retardant properties are tested according to GB / T 5454-1997.

[0042] Table 1 Nylon fiber fabric performance test After testing, the nylon fiber fabric of Comparative Example 1 had low moisture regain and limiting oxygen index, poor hygroscopicity and flame retardancy, and poor antibacterial properties. The nylon fiber fabrics of Examples 1 to 3 had high moisture regain, antibacterial rate, and limiting oxygen index, and showed better hygroscopicity, antibacterial and flame retardancy. This was mainly because the nylon fiber fabric was grafted with 2,4-bis-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methacrylamide] triazine containing an alkenyl group, which grafted hydrophilic amide bonds, imino groups, and a large number of hydroxyl groups onto the fabric surface, significantly improving the fabric's hydrophilicity and moisture absorption and moisture regain properties. In addition, the triazine group contains a large amount of nitrogen element, which releases nitrogen and other gases during combustion through thermal decomposition, which can dilute the oxygen concentration, inhibit combustion, and is beneficial to improving the limiting oxygen index and flame retardant properties. In addition, a large number of hydroxyl groups can interact with the hydroxyl groups on the surface of the titanium dioxide precursor generated by the hydrolysis of tetrabutyl titanate, so that the titanium dioxide precursor is evenly loaded onto the fabric surface. Further, after high-temperature hydrothermal method, the generated nano-titanium dioxide can be evenly loaded onto the fabric surface, exposing more photocatalytic antibacterial sites, significantly improving the antibacterial rate and antibacterial properties of Escherichia coli.

[0043] Comparative Example 2 did not utilize 2,4-bis-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methacrylamide] triazine to graft-modify the nylon fiber fabric, and did not graft amide bonds, imino groups, a large number of hydroxyl groups, and triazine groups to the fabric surface, resulting in a low regain and limiting oxygen index of the fabric, and poor dispersion of nano-titanium dioxide on the fabric surface, fewer photocatalytic antibacterial sites, resulting in a low antibacterial rate for Escherichia coli.

[0044] In Comparative Example 3, nylon fiber fabric was grafted and modified using hydroxyethyl acrylate. The nylon fiber fabric has a lower hydroxyl content and does not contain amide bonds, imino groups, and triazine groups. As a result, the moisture regain and limiting oxygen index of the fabric are lower than those in Example 1. In addition, the dispersion of nano-titanium dioxide on the surface of the fabric is poor, and there are fewer photocatalytic antibacterial sites, resulting in a lower antibacterial rate for Escherichia coli.

[0045] Comparative Example 4 uses 2,4-bis-(N,N'-diethylamino)-6-[N-(3-aminopropyl)methacrylamide] triazine to graft modify the nylon fiber fabric, which does not contain a large number of hydroxyl groups, resulting in a low moisture regain of the fabric, and poor dispersion of nano-titanium dioxide on the surface of the fabric, fewer photocatalytic antibacterial sites, resulting in a low antibacterial rate for Escherichia coli.

[0046] The above embodiments are intended only to illustrate the technical solutions of the present disclosure and are not intended to limit them. Although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they may modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents; and such modifications or replacements do not deviate from the spirit and scope of the technical solutions of the various embodiments of the present disclosure.

Claims

1. A method for preparing a moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric, characterized in that: The preparation method comprises: (1) The cleaned nylon fiber fabric is added to an aqueous solution of potassium persulfate for pre-reaction, and then the fabric is added to an aqueous solution containing 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-isotriazine, and the bath ratio A is adjusted to carry out a grafting reaction. Finally, the fabric is added to deionized water, boiled, washed with water, and dried to obtain a moisture-absorbing and perspiration-wicking nylon fiber fabric; (2) Tetrabutyl titanate was added to ethanol to prepare a tetrabutyl titanate solution, and a moisture-absorbing and perspiration-resistant nylon fiber fabric was added, and the bath ratio B was adjusted. After two immersion and two rolling treatments, the fabric was added to deionized water, and the bath ratio C was adjusted. After the reaction, the fabric was taken out, washed with ethanol and water, and dried to obtain a moisture-absorbing and perspiration-resistant antibacterial titanium fiber fabric.

2. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The concentration of the aqueous solution of potassium persulfate in (1) is (0.01-0.025) mol / L.

3. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The bath ratio A in (1) is 1:(35-50).

4. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The temperature of the pre-reaction in (1) is 70-80°C, and the reaction time is 20-40 minutes.

5. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The concentration of the aqueous solution of 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methylacrylamide]-1,3,5-s-triazine in (1) is (0.5-1.5) mol / L.

6. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The temperature of the grafting reaction in (1) is 65-80°C, and the reaction time is 2-3 hours.

7. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The mass fraction of the tetrabutyl titanate solution (2) is 20-30%; the bath ratio B is 1:(30-40), and the bath ratio C is 1:(30-50).

8. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 1, characterized in that: The reaction temperature in (2) is 90-95°C and the reaction time is 6-8h.

9. The method for preparing the moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric according to claim 5, characterized in that: The preparation method of 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine comprises: adding N-(3-aminopropyl)methacrylamide hydrochloride and 2,4-bis(N,N-dihydroxyethylamino)-6-chloro-1,3,5-s-triazine at a molar ratio of (1-1.2):1 to 1,4-dioxane, adding a sodium carbonate aqueous solution dropwise, heating to 75-85° C., reacting for 6-10 hours, cooling and filtering, rotary evaporating the filtrate, and recrystallizing the crude product from ethanol to obtain 2,4-bis(N,N-dihydroxyethylamino)-6-[N-(3-aminopropyl)methacrylamide]-1,3,5-s-triazine.

10. A moisture-absorbing, perspiration-wicking and antibacterial titanium fiber fabric obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for modifying nylon fabrics by adopting tetrabutyl titanate

    CN101876143A

  • Water-soluble triazine xanthic acid derivative, and preparation method and application thereof

    CN104529921A

  • Processing technology of wear-resistant and flame-retardant fabric

    CN113279109A

  • Antibacterial moisture-absorption modified polyester fabric as well as preparation method and application thereof

    CN118127662A

  • Antibacterial wear-resistant polyamide fiber and preparation method thereof

    CN118422369A